Evaluation of the Efficiency of Two Different Freezing Media and Two Different Protocols to Preserve Human Spermatozoa from Cryoinjury. (26th July 2016) - Fabozzi, Gemma; Starita, Maria Flavia; Rega, Emilia; Alteri, Alessandra; Colicchia, Antonio; Piscitelli, Claudio; Giannini, Pierluigi
Abstract : It is universally recognized that cryopreservation impairs sperm quality. In order to improve postthawing sperm survival and motility, media of different composition and different protocols have been proposed. However, no clear evidence is available to understand which are the most efficient protocol and medium for sperm cryopreservation. The present study evaluates the efficiency of two different cryopreservation protocols and two common freezing media (FM) containing different cryoprotectants (CPs), TEST Yolk Buffer (TYB) and Sperm Freeze (SF), to preserve human sperm quality. Our data suggest that TYB is better than SF both in terms of postthaw viability and in terms of progressive motility, while the direct addition of FM to the sperm sample resulted in the most efficient protocol in terms of postthaw viability but not in terms of progressive motility.